Bilingual guide to business and professional correspondence, German-English = Zweisprachen-Briefsteller fur das Geschaft und den Beruf, Englisch-Deutsch - Harvard, Joseph (Pergamon Oxford bilingual series, 1965)
Bilingual Guide to Business and Professional Correspondence: German-English presents a selection of sentences and phrases that are essential for writing business letters. The book is comprised of nine chapters; each chapter addresses a specific aspect of business communications. The text first presents the lay-out of a German business letters, and then proceeds to tackling the contents of a business letter. The subsequent chapters deal with various concerns in business communications, such monetary concerns, legal matters, business transactions, applications, and business relations. The book w.